The Influence of Product Quality, Service Quality, and Price Towards Customer Purchase Decision at Starbucks Coffee in Diponegoro Medan - Justin; Jocelyn; Tifanny Husin; Tessa Monica Sidauruk (International Journal of Economics, Business Management and Accounting (IJEBMA), 2021)
The effect of service quality has a significant positive effect on Starbucks Coffee customer purchase decision at Diponegoro Medan, meaning that the better the service, the higher the level of satisfaction obtained by consumers. This is reasonable because consumers always see the most important in terms of service quality. The effect of product quality has a significant positive effect on Starbucks Coffee customer purchase decision in Diponegoro, Medan meaning that the better the product quality, the higher the level of satisfaction created and obtained by consumers. This is reasonable because consumers feel their desires are fulfilled in product quality. The effect of price has a positive but not significant effect on Starbucks Coffee customer purchase decision in Diponegoro, Medan meaning that consumers are indeed satisfied with the quality of service and product quality created, but consumers do not see much from the Starbucks price perspective. Consumers see more in terms of services and products provided